2022
DOI: 10.3390/en15196913
|View full text |Cite
|
Sign up to set email alerts
|

Remuneration Sensitivity Analysis in Prosumer and Aggregator Strategies by Controlling Electric Vehicle Chargers

Abstract: The efficient use of energy resources is profoundly changing power grid regulation and policy. New forms of power generation coupled with storage and the presence of new, increasingly flexible loads such as electric vehicles enable the development of multi-agent planning systems based on new forms of interaction. For instance, consumers can take advantage of flexibility by interacting directly with the grid or through aggregators that bridge the gap between these end-users and traditional centralised markets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The data points represent the energy demand during the drive per km for distinct values of the ambient temperature. The resulting polynomial coefficients α, β, γ, ϵ, ζ, and θ of the functions in (19) and (20) are defined and listed in Table IV.…”
Section: Specific Driving Energy Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…The data points represent the energy demand during the drive per km for distinct values of the ambient temperature. The resulting polynomial coefficients α, β, γ, ϵ, ζ, and θ of the functions in (19) and (20) are defined and listed in Table IV.…”
Section: Specific Driving Energy Demandmentioning
confidence: 99%
“…This enables aggregation entities to define and implement smart charging strategies for EVs. Prior research showed how to design smart charging strategies [12]- [20] to reduce the overall energy cost, avoid grid congestions, circumvent peak loads due to the charging processes, and provide frequency regulation services [6], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Equation (9) indicates that the EV increases the charging power in response to the downward scheduling of the grid in this scheduling interval, but its charging power cannot be so large that the battery SOC exceeds the upper limit, otherwise it will damage the battery life. Combining the power constraint (10) leads to the formula (11) for the threshold value of the downward SC.…”
Section: • Threshold For Downward Sc Of An Evmentioning
confidence: 99%
“…EVs usually participate in grid dispatch through aggregators. [11] presents the mathematical formulation of the different prosumers and proposes the aggregation strategies, providing a guideline for the payment options of future users to be involved in aggregator schemes. A crucial step in realizing the interaction of EVs with the grid is the quick and accurate forecast of the schedulable capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The EV aggregator manages a population of EVs in a centralized system [8,9]. The centralized system employs a control center to collect the information from all available EVs and controls when and at what rate each EV will charge or discharge [10,11]. Although the regulation capacity of an individual EV is small, large-scale aggregated EVs provide considerable regulation capacity and rapid responding speed for regulating the power system frequency [12].…”
Section: Introductionmentioning
confidence: 99%